Verba krist daudznozīmība latviešu valodā - Kuplā, Ieva (Baltistica, 2012)
POLYSEMY OF THE VERB krist ‘FALL’ IN THE LATVIAN LANGUAGESummaryThis article describes one of the fundamental problems of lexicography: the representation of polysemy in dictionaries. Often the number of word meanings differs in explanatory dictionaries. For instance, the number of meanings of the verb krist ‘fall’ found in the “Dictionary of the Latvian Literary Language” is 24, in the “Dictionary ofthe Latvian Language” – 17 and in the “Dictionary of the Contemporary Latvian Language” – 18 meanings.Different research methods are applied in the analysis of the meaning system of the verb krist. In the article relations of the word meanings are analyzed paradigmatically, by applying the method of semantic component analysis, and syntagmatically, by applying the semantic conjunction approach. In addition, word meaning relations are analyzed by applying the prototype theory of cognitive linguistics.After the analysis of definitions of the verb krist in the explanatory dictionaries of the Latvian language as well as the analysis of examples of the verb krist in the contemporary Latvian language corpus, the author concludes that it is possible to form a meaning system of the verb krist comprising 8 meanings.